Contemporary trends in mediation & arbitration in Asia Pacific - Rashid, Syed Khalid (IIUM Press, 2009)
Conferences and seminars are organized to bring together scholars and professionals who have the ability to perceive problems in a given field with the aim of searching possible solutions. With this aim the Asia Pacific conference on the Contemporary Trends in Mediation and Arbitration in the Asia Pacific was organized. Sixteen papers have been selected out of the many presented at the conference for inclusion in this book, which also contains conference proceedings and two appendices. I have edited this book. As many as 13 papers out of 16 contained in the book dealt with mediation, while the remaining 3 dealt with arbitration. It is indicative of the things to come. Mediation is fast becoming the preferred mode of dispute settlement in the whole of Asia Pacific region. The inexpensiveness and simplicity of mediation make it poles above arbitration, which is becoming increasingly costly, cumbersome, protracted and technical, thereby losing much of its charm. The papers on mediation in the book first dealt with the basic questions of mediation education, training, practice and accreditation, followed by country reports covering India, Japan, Philippines, Singapore, Russia, Malaysia and Hong Kong. One of the papers on India covers amicable settlement of dispute in the Indian Universities and the other covers the unique system of qada and ifta as tools of dispute settlement. The three papers on arbitration cover the working of the Kuala Lumpur Regional Centre for Arbitration, and the status of arbitration in Vietnam and Malaysia. The over-all thrust of the book is to examine the current status of mediation and arbitration in Asia Pacific and to explore the possibility of finding solutions to the existing problems in these two areas.